2002
DOI: 10.1046/j.1365-2141.2002.03673.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantification improves the prognostic value of CD38 expression in B‐cell chronic lymphocytic leukaemia

Abstract: Summary. Recent studies have shown that CD38 expressed as a percentage of the antigen positivity can predict prognosis and disease progression in patients with B‐cell chronic lymphocytic leukaemia (B‐CLL). The present study showed that quantification of CD38 expressed as antibody‐binding capacity (ABC) improves the prognostic value of the percentage of CD38 positivity in B‐CLL. In a cohort of 81 patients with B‐CLL, a level of CD38 expression of ≥ 30% and an ABC value of 250 proved statistically valid cut‐off … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 24 publications
3
18
0
1
Order By: Relevance
“…Among the HLA-B alleles, HLA-B52:01 allele was expressed at a higher frequency in CLL patients expressing CD38 molecule, compared to CD38 -patients (OR=4.77, p=0.037). Association between expression of CD38 and/or lack of IGHV mutation with disease progression has been reported in various studies [7,43,44]. Accordingly, HLA-A32:01, A33:01 and B52:01 alleles seem to be positively associated to disease progression in our CLL patients.…”
Section: Discussionsupporting
confidence: 65%
“…Among the HLA-B alleles, HLA-B52:01 allele was expressed at a higher frequency in CLL patients expressing CD38 molecule, compared to CD38 -patients (OR=4.77, p=0.037). Association between expression of CD38 and/or lack of IGHV mutation with disease progression has been reported in various studies [7,43,44]. Accordingly, HLA-A32:01, A33:01 and B52:01 alleles seem to be positively associated to disease progression in our CLL patients.…”
Section: Discussionsupporting
confidence: 65%
“…This quantification can be achieved by measuring CD38 ABC (antibodies bound per cell). The first study on CD38 ABC of leukemic cells in CLL patients was published in 2002 by Mainou-Fowler et al (8). A significant shorter time to first treatment and a shorter disease-specific survival was seen in patients with more than 250 ABC as compared to those with less than 250 ABC.…”
mentioning
confidence: 99%
“…CD38 expression was also initially reported by Damle et al. to be correlated with IgV H mutations [1], however subsequent studies showed only some degree of correlation [6,7]. Irrespective of the extent of concordance with rearrangement of the IgV H genes, CD38 expression was proved by many investigators to be a reliable predictor of the outcome in B-CLL [8,9].…”
Section: Introductionmentioning
confidence: 95%